Hollow earth - Bone quill - Barrowman, John 1968-; Barrowman, Carole 1959- (Aladdin, 2013)
"Twins Matt and Em are animare. They have the ability to bring art to life, but someone wants to use their power to unleash demons from Hollow Earth where they are locked away. A journey through time will be necessary if Matt and Em are to stop this plot"..
"Originally published in Great Britain in 2013. Published by arrangement with Buster Books, an imprint of Michael O'Mara Books Limited.". - Sequel to: Hollow Earth
Keywords: JUVENILE FICTION / Fantasy & Magic; JUVENILE FICTION / Action & Adventure / General; JUVENILE FICTION / Family / Siblings; Kunst; Magic; Art; Twins; Brothers and sisters; Schottland; Scotland; Jugendbuch